United Nations Global Compact: an ‘Inroad’ into the UN and reputation boost for the tobacco industry - van der Eijk, Yvette (Tob Control, 2017)
BACKGROUND: The United Nations Global Compact (UNGC), a UN initiative to engage corporations in supporting the UN’s mission, sets out principles that companies should follow for more ethical business practices. Since its inception in 2000, at least 13 tobacco companies, subsidiaries and tobacco industry affiliates joined the UNGC. In a September 2017 integrity review, the UNGC Board excluded from UNGC participation companies who derive revenue from tobacco production or manufacturing. OBJECTIVE: To determine, from the tobacco industry’s perspective, tobacco companies’ motives for joining the UNGC. METHOD: Tobacco industry documents search using the Truth Tobacco Industry Documents Library, and search of published reports and documents on the tobacco industry and the UNGC. RESULTS: Tobacco companies sought to join the UNGC for two reasons: (1) to improve their reputation, in keeping with other corporate social responsibility efforts; (2) to gain proximity to UN agencies and weaken the WHO’s influence, part of an overall strategy to undermine the WHO Framework Convention on Tobacco Control. CONCLUSIONS: Excluding tobacco manufacturers from UNGC participation is an important step to limit the tobacco industry’s ability to influence the UN and promote its image and, by extension, its deadly products. It is important to monitor enforcement of this policy and resist the engagement of tobacco industry front groups, such as industry-funded foundations, with the UNGC.